On the concordance between CAPS-5 and PCL-5 scores - Daniel J. Lee; Frank W. Weathers; Michelle J. Bovin; Brian P. Marx (European Journal of Psychotraumatology)
Background: As reported in this journal, Resick and colleagues (2023) investigated discrepancies between scores from two widely used PTSD measures: the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5; Weathers et al., 2013) and the PTSD Checklist for DSM-5 (PCL-5; Weathers et al., 2013), a clinician-rated structured interview and a self-rated questionnaire, respectively. Using data from four clinical trials of active-duty military personnel and veterans, the authors replicated the common finding that PCL-5 scores are higher than CAPS-5 scores. They then examined item response distributions, finding that ratings on the PCL-5 were more evenly distributed across all five options whereas specific CAPS-5 scores were used relatively infrequently. Concluding that this finding indicates a problem that should be addressed, they offered suggestions for revising anchors and items to improve correspondence between the two measures.Objective: The results are informative and the nature and size of the sample are well-suited to this important research question. However, we have a number of concerns and comments about this paper.Conclusion: In our view, the authors mischaracterized the CAPS-5 and PCL-5 in several important ways, resulting in some erroneous conclusions about their findings and the expected nature of the relationship between the CAPS-5 and PCL-5. Given that these issues are vital to the field of traumatic stress, we felt compelled to address them and provide an alternative perspective.